A Study to Determine the Mediating Effect of Novelty Seeking in the Effect of Consumers’ Personal Values on Attitudes Towards Functional Foods - Selçuk Efe Küçükkambak (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
In research conducted in the field of consumer behavior, some of the common goals of researchers are to determine the factors that affect the purchasing decision process of consumers, to monitor the current changes of these factors, to identify the variables that affect these factors, and to try to reveal the dark motives of the consumer that affect the purchasing decision. In the studies carried out in the field of consumer behavior from past to present, the process that directs individuals to purchase has been discussed in various aspects. One of the most important factors for researchers in these studies is the attitudes that lead consumers to purchasing behavior. Attitudes are one of the most important consumer decisions that can affect the purchasing decision positively or negatively. There are many factors that can affect consumers' attitudes towards a particular product or service. One of the factors shaping consumer attitudes is personal values, which are seen as a part of consumers' lifestyle. Although the concept of personal value is included in the theories in the field of social psychology, it has become one of the concepts that are discussed more frequently in studies on consumer behavior. In this study, it was aimed to determine the role of novelty seeking behaviors in the attitudes of consumers' personal values towards functional foods. In the research process, mixed research method, in which quantitative and qualitative methods are carried out together, was preferred. Within the scope of the research, the data collected from 470 people using the online survey method and snowball sampling were analyzed with the structural equation model. According to the results of the analysis, it has been determined that the novelty seeking behaviors have a full mediating effect on the personal values of openness to changes and conservation values of consumers' attitudes towards functional foods. In the light of the data obtained within the scope of the research, some inferences were made to the marketing managers and suggestions were presented to the researchers for future studies. It is expected that the findings obtained as a result of the research will contribute to the literature in terms of revealing the effects of personal values and innovation seeking behavior on consumers' attitudes towards innovative products.